1992
DOI: 10.1210/endo.130.6.1597135
|View full text |Cite
|
Sign up to set email alerts
|

Dietary potassium supplementation and sodium restriction stimulate aldosterone synthase but not 11 beta-hydroxylase P-450 messenger ribonucleic acid accumulation in rat adrenals and require angiotensin II production.

Abstract: Increasing evidence indicates that the adrenal cortex of most mammalian species expresses distinct forms of cytochrome P-450(11 beta), a steroidogenic enzyme that catalyses the terminal steps in the biosynthesis of both glucocorticoids and mineralocorticoids. In the human, mouse, and rat, two genes have been isolated, designated CYP11B1 and CYP11B2. The product of CYP11B2 (aldosterone synthase) is required for the successive 11 beta-, 18-hydroxylations and 18-oxidation of deoxycorticosterone that lead to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…15 years later, Boyd et al (21) documented some 0.5 mEq/liter increase in plasma potassium level during dietary salt restriction and speculated on an intermediary role of potassium in the secondary hyperaldosteronism. However, studies (1)(2)(3)22) have since demonstrated that the attempt to inhibit Ang II by a pharmacological measure is commonly effective in reversing the hyperaldosteronism, leading to the current prevailing notion that the role of potassium in this condition, if any, is channelled through the action of the renin-angiotensin system (23).…”
Section: Introductionmentioning
confidence: 99%
“…15 years later, Boyd et al (21) documented some 0.5 mEq/liter increase in plasma potassium level during dietary salt restriction and speculated on an intermediary role of potassium in the secondary hyperaldosteronism. However, studies (1)(2)(3)22) have since demonstrated that the attempt to inhibit Ang II by a pharmacological measure is commonly effective in reversing the hyperaldosteronism, leading to the current prevailing notion that the role of potassium in this condition, if any, is channelled through the action of the renin-angiotensin system (23).…”
Section: Introductionmentioning
confidence: 99%
“…The second is that the local expression of adrenal renin is required for normal ZG function (7,9,10,14,16,26,28,29,31). One of the theories is that local generation of adrenal ANG II mediates the ZG response to increases in potassium and that this is mediated by AT 1 -type angiotensin receptors (14,26,29).…”
Section: Discussionmentioning
confidence: 99%
“…The classic renal renin-angiotensin-aldosterone system (RAAS) is well known as a major regulator of sodium and potassium balance. However, it has been known for decades that the adrenal cortex also expresses a local RAAS that operates independently of the renal RAAS (2,7,9,14,16,26,28). One theory is that adrenal renin-generated ANG II mediates the ZG response to increases in plasma potassium, and this is mediated by expression of the angiotensin AT 1 receptor (5,9,14,26,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This fact was reinforced more recently by Tremblay et al (1992) who demonstrated that potassium supplementation or sodium restriction in rats increased aldosterone synthase but not 1 ID-hydroxylase P-450 mRNA. It should be noted that under both regimens angiotensin I1 was required, as captopril blocked these responses.…”
Section: Aldosterone Synthase Effectsmentioning
confidence: 89%